Simultaneous determination of pesticides in fruits by using second-order fluorescence data resolved by unfolded partial least-squares coupled to residual bilinearization - Villar Navarro, Mercedes (2018)
Fil: Villar Navarro, Mercedes. Universidad de Sevilla. Facultad de Química. Departamento de Química Analítica; España